UTAUT2 모형을 적용한 대학생들의 온라인 스포츠 미디어 사용행동 분석 - 변현; Hyun Byun; 조광민; Kwang Min Cho; 배정섭; Jung-sup Bae (Ch'eyuk kwahak yŏn'gu, 2017)
[목적] 본 연구는 Unified theory of acceptance and use of technology2(UTUAT2) 모형을 적용하여 구조적 관계 탐색을 통해 대학생들의 온라인 스포츠 미디어 이용행동을 검증하는데 그 목적이 있다. [방법]연구를 위해 서울에 소재한 대학교 학생들을 표본 집단으로 선정하였으며, 총 235명의 설문지를 확보하여 가설을 검증하였다. 자료 분석에는 빈도분석, 신뢰도 분석, 확인적 요인분석, 상관관계 분석, 및 구조방정식모형분석을 실시하였다. [결과] 이에 따른 분석결과는 다음과 같다. 첫째, 성과기대와 노력기대는 사용의도에 정(+)의 영향을 미친 반면 사회적 영향은 유의미한 영향을 미치지 않는 것으로 나타났다. 둘째, 촉진조건은 사용행동에 유의미한 영향을 미치지 않는 것으로 나타났다. 셋째, 쾌락적 동기는 지속적 사용의도에 정(+)의 영향을 미치는 것으로 나타났다. 넷째, 습관은 지속적 사용의도와 사용행동에 정(+)의 영향을 미치는 것으로 나타났다. 마지막으로 지속적 사용의도는 사용행동에 정(+)의 영향을 미치는 것으로 나타났다. [결론] 본 연구의 결론을 바탕으로 온라인 스포츠 미디어 기업은 개인화된 서비스를 제공함으로서 유용하고 편리한 시청경험을 제공해야 하며, 습관적으로 스포츠 온라인 미디어를 사용할 수 있도록 다양한 유인전략을 적용해야 할 것이다. [Purpose] The purpose of this study was to investigate the factor that influence the using behavior of online sport media by university students applying Unified theory of acceptance and use of technology 2(UTAUT 2). [Methods] The study performed a research survey using convenient sampling method. The sample was 235 university students who had experience with online sport media. The data were analyzed through frequency analysis, reliability analysis, correlation analysis, confirmatory factor analysis, and structural equation model using SPSS Windows ver . 20.0 and AMOS 20.0. [Results] The results showed that, firstly, performance expectancy and effort expectancy had a positive effect on intention to use, however, no significant influence on social effect on intention to use. Secondly, facilitating condition had positive effect on usage behavior. Thirdly, hedonic motivation had positive effect on intention to use. Fourthly, Habit had positive effect on the intention to use and usage behavior. Lastly, intention to use had positive effect on usage behavior. [Conclusion] Based on the conclusion of this study, online sports media companies should provide useful and convenient viewing experience by providing personalized services, and should apply various attraction strategies to habitually use sports online media.